PrbP modulates biofilm formation in Liberibacter crescens - Pan, Lei (2021)
In Liberibacter asiaticus, PrbP is a transcriptional regulatory protein involved in survival and persistence during host infection. Tolfenamic acid was previously found to inhibit interactions between PrbP and the promotor region of rplK, resulting in reduced survival of L. asiaticus in the citrus host. In this study, we performed transcriptome analyses to elucidate the PrbP regulon in L. crescens, as it is phylogenetically the closest related species to L. asiaticus that can be grown in laboratory conditions. Chemical inhibition of PrbP with tolfenamic acid revealed that PrbP is involved in the regulation of diverse cellular processes, including stress response, cell motility, cell cycle and biofilm formation. In vitro DNA binding and bacterial two-hybrid assays also suggested that PrbP is a global regulator of multiple transcription factors (RpoH, VisN, PleD, MucR, MocR and CtrA) at both transcriptional and/or post-transcriptional levels. Sub-lethal concentrations of tolfenamic acid significantly reduced the attachment of L. crescens during biofilm formation and decreased long-term persistence in biofilm structures. Overall, our findings show the importance of PrbP in regulating diverse biological processes through direct and indirect interactions with other transcriptional regulators in L. crescens.